2019
DOI: 10.20960/nh.02640
|View full text |Cite
|
Sign up to set email alerts
|

Interleukine 6 and C-reactive protein predict growth impairment and acute malnutrition in children and adolescents with chronic kidney disease

Abstract: Interleukine 6 and C-reactive protein predict growth impairment and acute malnutrition in children and adolescents with chronic kidney disease La interleucina 6 y la proteína C-reactiva predicen el retraso del crecimiento y la desnutrición aguda en niños y adolescentes con enfermedad renal crónica

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In children suffering from CKD, the development of anaemia was inversely correlated with IL-6 concentration [ 101 ]. Additionally, IL-6 predicted acute malnutrition and growth impairment among children and adolescents with CKD [ 102 ]. Certain studies revealed a possible link between IL-6 and pruritus occurrence due to chronic sulphur mustard exposure [ 103 ] and in the course of prurigo nodularis (PN) [ 104 ].…”
Section: Pathogenesis Of Ckd-aimentioning
confidence: 99%
“…In children suffering from CKD, the development of anaemia was inversely correlated with IL-6 concentration [ 101 ]. Additionally, IL-6 predicted acute malnutrition and growth impairment among children and adolescents with CKD [ 102 ]. Certain studies revealed a possible link between IL-6 and pruritus occurrence due to chronic sulphur mustard exposure [ 103 ] and in the course of prurigo nodularis (PN) [ 104 ].…”
Section: Pathogenesis Of Ckd-aimentioning
confidence: 99%